Activation of JAK2 tyrosine kinase by prolactin receptors in Nb2 cells and mouse mammary gland explants. - Campbell, G S (1994)
One of the earliest cellular responses to prolactin (PRL) binding in Nb2 cells, a rat pre-T lymphoma cell line, is an increase in tyrosine phosphorylation of cellular proteins. In this work, immunologic techniques have been used to demonstrate that in Nb2 cells and in mouse mammary gland explants, JAK2, a non-receptor tyrosine kinase, is activated following stimulation with PRL. PRL stimulated tyrosine phosphorylation of JAK2 at times as early as 30 sec and concentrations of PRL as low as 0.5 ng/ml (2.5 pM) in Nb2 cells and 100 ng/ml (5 nM) in mammary gland explants. When JAK2 was immunoprecipitated from solubilized Nb2 cells or mammary gland explants and incubated with [gamma-32P]ATP, 32P was incorporated into a protein migrating with an apparent molecular weight appropriate for JAK2 only when cells had been incubated with PRL, indicating that JAK2 tyrosine kinase activity is exquisitely sensitive to PRL. In Nb2 cells, JAK2 was found to associate with PRL receptor irrespective of whether or not the cells had been incubated with PRL. These results provide strong evidence that JAK2 is constitutively associated with the PRL receptor and that it is activated and tyrosine phosphorylated upon PRL binding to the PRL receptor. These results are consistent with JAK2 serving as an early, perhaps initial, signaling molecule for PRL.